2009
DOI: 10.1097/meg.0b013e32832a4e97
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon alpha-2b and ribavirin for the treatment of chronic hepatitis C in Japanese pediatric and young adult patients: a survey of the Japan Society of Pediatric Hepatology

Abstract: The results showed that the present patients infected with HCV and treated with peginterferon-2b and ribavirin achieved a remarkably high SVR rate. In addition, most of the patients achieved a SVR once they showed a virologic response at week 4. The combination of peginterferon-alpha with ribavirin may be considered as a standard therapy for children and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(61 citation statements)
references
References 28 publications
2
57
0
2
Order By: Relevance
“…Although combination therapy with ribavirin and pegylated interferon, which is recommended as a standard regimen for pediatric and young adult patients with chronic hepatitis C (CHC) worldwide [29,30,31,32], high ribavirin doses increase the risk of hemolytic anemia [33]. Suzuki M et al [34] selected 12 CHC patients who received the combination therapy to evaluate the efficacy of EPA on ribavirin-induced hemolytic anemia, and they found that the hemoglobin levels were significantly improved in the EPA group at 8 and 16 weeks, contributing to avoiding ribavirin-related anemia .…”
Section: Liver Protectionmentioning
confidence: 99%
“…Although combination therapy with ribavirin and pegylated interferon, which is recommended as a standard regimen for pediatric and young adult patients with chronic hepatitis C (CHC) worldwide [29,30,31,32], high ribavirin doses increase the risk of hemolytic anemia [33]. Suzuki M et al [34] selected 12 CHC patients who received the combination therapy to evaluate the efficacy of EPA on ribavirin-induced hemolytic anemia, and they found that the hemoglobin levels were significantly improved in the EPA group at 8 and 16 weeks, contributing to avoiding ribavirin-related anemia .…”
Section: Liver Protectionmentioning
confidence: 99%
“…A formal paper has not been published yet, but the main results of the study have been presented at the 59th Annual Meeting of the American Association for the Study of Liver Diseases 76. Two further studies described small cohorts of children with chronic hepatitis C treated with peginterferon-á-2b and ribavirin 77,78. The first, published by Baker et al, is a retrospective/prospective study reporting observations on 10 adolescents.…”
Section: Combined Treatment With Peginterferon-á and Ribavirinmentioning
confidence: 99%
“…The first, published by Baker et al, is a retrospective/prospective study reporting observations on 10 adolescents. The second is a retrospective, multicenter, collaborative study by the Japan Society of Pediatric Hepatology on 33 children and young adults 78. Two more studies on combined treatment have been published, but were excluded from the analysis performed in this review, in one case because it was not possible to extrapolate the children treated with peginterferon-á-2a and those treated with peginterferon-á-2b79 and the other because the patients enrolled were on treatment at the end of the follow-up 54…”
Section: Combined Treatment With Peginterferon-á and Ribavirinmentioning
confidence: 99%
See 2 more Smart Citations